The Essential Guide to Rockpooling - Hatcher, Julie (Wild Nature Press Ser., 2019)
"This book reveals the astonishing diversity of wildlife on rocky shores and in the rockpools around the coast of Britain and gives readers a greater under-standing of the myriad creatures that can be found using a bit of simple detective work. Rockpooling is an activity enjoyed by children and adults alike. This guide will make your exploration even more rewarding, whether you are enjoying a day out at the seaside or seeking to expand your knowledge of a unique habitat. ​​​​​​Includes: Detailed descriptions of around 400 common and rare rocky shore species; clear colour photographs of all the species; tips and techniques describing how to find the more cryptic animals described; ideas for rockpool-related family activities; information on threats to the intertidal environment."--Back cover.